Pengaruh Ketersediaan Air Bersih dan Responsif Keluhan terhadap Kepuasan Pelanggan Perumda Air Minum Wair Pu’an di Desa Lepo Lima - Nikodemus Rikardo Lero; Antonius Philipus Kurniawan; Yosef Tonce (Jurnal CUAN Universitas Nusa Nipa Maumere, 2024)
This research aimed to (1) describe the availability of clean water, complaint responsiveness, and customer satisfaction; (2) analyze the significant influence of clean water availability and complaint responsiveness on customer satisfaction. The population in this research was the customers of Perumda Air Minum Wair Pu'an in Lepo Lima vilage. Due to the indefinite population size, a sample ef 100 respondents was taken. Data were collected through questionnaires and analyzed using descriptive inferential methods, specifically multiple linear regression. Hypothesis testing was conducted through F-tests and t-tests. The results of the descriptive analysis revealed that the variables of clean water availability, complaint responsiveness, and customer satisfaction were categorized as good. The t-test statistical analysis demonstrated that both clean water availability and complaint responsiveness had a positive and significant impact on customer satisfaction. Furthermore, the F-test statistical results indicated that all independent variables collectively had a significant effect on customer satisfaction. The determination analysis revealed that the contribution of clean water availability and complaint responsiveness. to customer satisfaction at Perumda Air Minum Wair Pu'an in Lepo Lima Village was 54.2%. while the remaining 45.8% was influenced by other factors beyond the scope of the research variables.